DETERMINATION OF RESOLUTION LIMITS OF ELECTRICAL TOMOGRAPHY ON THE BLOCK MODEL IN A HOMOGENOUS ENVIRONMENT BY MEANS OF ELECTRICAL MODELLING - Franjo Šumanovac; Snježana Dominković Alavanja (Rudarsko-geološko-naftni Zbornik, 2007)
The block model in a homogenous environment can generally serve for presentation of some geological models: changes of facies, changes of rock compactness-fragmentation, underground cavities, bauxite deposits, etc. Therefore, on the block model of increased resistivities in a homogenous environment of low resistivity, the potentials of the electrical tomography method were tested for the purpose of their detection. Regarding potentials of block detection, resolution methods depend on: depth of block location, ratio between block resistivity and the environment in which it is located as well as applied survey geometry, i.e. electrode array. Thus the analyses carried out for the most frequently used electrode arrays in the investigations are the following: the Wenner, Wenner-Schlumberger, dipole-dipole and pole-pole arrays. For each array, maximum depths at which a block can be detected relative to the ratio between block resistivity and parent rock environment were analyzed. The results are shown in the two-dimensional graphs, where the ratio between the block resistivity and the environment is shown on the X-axis, and the resolution depth on the Y-axis, after which the curves defining the resolution limits were drawn. These graphs have a practical use, since they enable a fast, simple determination of potentials of the method application on a specific geological model.